Chemical Composition, Larvicidal and Repellency Properties of Cionura erecta (L.) Griseb. Against Malaria Vector, Anopheles stephensi Liston (Diptera: Culicidae). - Ehssan Mozaffari; Mohammad Reza Abai; Mahnaz Khanavi; Hassan Vatandoost; Mohammad Mehdi Sedaghat; Abbas Moridnia; Mahsa Saber-Navaei; Alireza Sanei-Dehkordi; Fatemeh Rafi (Tehran University of Medical Sciences, 2014)
Background: Application of plant derivatives have been suggested as alternative sources for mosquito control. Methods: The root essential oil and methanol extract of Cionura erecta (L.) Griseb was tested under laboratory conditions for larvicidal and skin repelleny activities against Anopheles stephensi. The chemical compositions of essential oils were analyzed using gas chromatography- mass spectrometry. Results: Among the five concentrations tested, the 320 ppm of essential oil and 1280 ppm of methanolic extract had the most toxic effects yielding 100% mortality. The LC50 values of C. erecta for both essential oil and methanolic extract were 77.30 and 250.38 ppm, respectively. A total of 19 compounds were identified in essential oil of root. The major components were detected in root essential oil including Cedren-9-one (7.89%), alpha cadinol (5.67%), eugenol (4.02%) and alpha muurolene (3.58%). The protection time of 50% solution of essential oil against bites of An. stephensi was 2.28 hour on white rabbit and the ED50 and ED90 values of the essential oil were 10.12 and 23.01 ppm respectively. Conclusion: The findings suggest that C. erecta oil has a potential source as larvicidal and repellency properties against An.stephensi.